Combining Hepatic Arterial Interventional Therapies with Lenvatinib and Programmed Cell Death-1 Inhibitors for Hepatocellular Carcinoma with Portal Vein Tumor Thrombosis: A Single-Center, Real-World Study - Shen X; Shao T; Yu J; Zhang Z (Journal of Hepatocellular Carcinoma, 2025)
Xuehan Shen,* Tianyin Shao,* Jun Yu, Zhiwei Zhang Hepatic Surgery Center, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiwei Zhang, Hepatic Surgery Center, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1095 Jiefang Avenue, Wuhan, 430030, People’s Republic of China, Email zwzhang@tjh.tjmu.edu.cnBackground and Purpose: The survival of hepatocellular carcinoma (HCC) patients with portal vein tumor thrombosis (PVTT) was poor. This study aimed to investigate the efficacy and safety of hepatic arterial interventional therapies (HAIT) combined with lenvatinib and programmed cell death-1 (PD-1) inhibitors for HCC patients with PVTT.Methods: In this retrospective study, HCC patients with PVTT treated with HAIT combined with lenvatinib and PD-1 inhibitors (H-L-P group) or lenvatinib plus PD-1 inhibitors (L-P group) between June 2020 and December 2023 were analyzed. Overall survival (OS), progression-free survival (PFS), and tumor response were evaluated to assess the efficacy, while treatment-related adverse events (TRAEs) were evaluated to assess the safety. Propensity score matching (PSM) was applied to balance the baseline differences.Results: In this study, 208 HCC patients with PVTT were enrolled, including 120 patients in H-L-P group and 88 patients in L-P group. After PSM, there were 74 patients per group, the H-L-P group showed significantly better median OS (19 months vs 14 months, p < 0.001) and median PFS (10 months vs 4 months, p < 0.001) than L-P group; higher objective response rate (ORR) (37.8% vs 16.2%, p < 0.001) and disease control rate (DCR) (78.4% vs 47.3%, p < 0.001) were observed in the H-L-P group. All TRAEs were controlled, and the three most prevalent TRAEs in the H-L-P group were elevated aspartate aminotransferase (AST), elevated alanine aminotransferase (ALT), and vomiting.Conclusion: Combining HAIT with lenvatinib and PD-1 inhibitors is a safe and promising treatment pattern for HCC patients with PVTT.Keywords: hepatocellular carcinoma, hepatic arterial interventional therapies, lenvatinib, programmed cell death protein-1 inhibitors, portal vein tumor thrombosis